Síntese de 4-(1-fenil-5-trifluormetil-1h-pirazol-4-il)-1h-1,2,3-triazóis promovida por dialquil biaril fosfinas e catálise metálica - Dal Forno, Gean Michel (2017)
The present dissertation describes the development of a three-step, one-pot methodology, involving the sequential reactions of Sonogashira cross-coupling, deprotection of terminal alkyne (removal of trimethylsilane group), and copper salt catalyzed azide-alkyne cycloaddition (CuAAC) in obtaining a series of fifteen new examples of 4-(5-(trifluoromethyl)-1H-pyrazol-4-yl)-1H-1,2,3-triazoles in yields of 29-72%. The present methodology comprises of obtaining, initially, three examples of 3-methyl(aryl)-1-phenyl-5-trifluoromethyl-1H-pyrazoles, where aryl = Ph and 4-FC6H4, in 86 – 92% yields, from cyclocondensation reaction [3+2] between 4-alkoxy-1,1,1-trifluoro-3-alken-2-ones and phenylhydrazine. Subsequently, the 3-substituted-1-phenyl-5-trifluoromethyl-1H-pyrazoles were used for the synthesis of 3-methyl(aryl)-4-bromo-1-phenyl-5-trifluoromethyl-1H-pyrazoles, in yields of 92 – 95%, by electrophilic bromination reaction using N-bromosuccinimide (NBS). The heterocycle 4-bromo-1-phenyl-5-trifluoromethyl-1H-pyrazole was obtained from the cyclocondensation [3+2] of 3-bromo-4-ethoxy-1,1,1-trifluoro-3-buten-2-one and phenylhydrazine in 38% yield. The optimization of the stepwise reaction for the synthesis of the 1- alkyl(aryl)-4-(3-methyl(aryl)-1-phenyl-5-(trifluoromethyl)-1H-pyrazol-4-yl)-1H-1,2,3-triazoles series was possible by evaluating the catalytic activity of palladium complexes with five different dialkylaryl phosphines in Sonogashira cross-coupling reaction between 4-bromo-1-phenyl-5-trifluoromethyl-1H-pyrazole and ethynyltrimethylsilane. This step showed that dicyclohexyl(2',4',6'-triisopropyl-[1,1'-biphenyl]-2-yl)phosphine (Xphos) is the best performance catalyst for the studied coupling, allowing the isolation of 3-methyl-1-phenyl-5-(trifluoromethyl)-4-((trimethylsilyl)ethynyl)-1H-pyrazole in 83% yield. In the final step, a deprotection reaction using CsF followed by a cycloaddition reaction (CuAAC) in the presence of benzyl azide afforded the preparation of 1-benzyl 1-benzyl-4-(5-(trifluoromethyl)-1H-pyrazol-4-yl)-1H-1,2,3-triazole as the final product in 72% yield. After the step by step optimization was carried out a three-step one-pot methodology was used to construct the series of 4-(5-(trifluoromethyl)-1H-pyrazol-4-yl) -1H-1,2,3-triazoles (15 examples).